(untitled) (ALPHA. Journal of Arts, Literature and Philosophy, 2018)
The arrival of the Transandean Railway influenced the aesthetic perception that passers-by formed of the local geography. The mountain appears as a fundamental element of poetry in various authors, including Chilean poet Gabriela Mistral. The mountains and its access, from the Elqui to the Andes, are a core element of her poetry, acquiring particular characteristics at each stage of her poetic creation and political vision, which will be analyzed in this article.